2019
DOI: 10.1002/chem.201904491
|View full text |Cite
|
Sign up to set email alerts
|

Spirobifluorene‐Based o‐Carboranyl Compounds: Insights into the Rotational Effect of Carborane Cages on Photoluminescence

Abstract: 9,9′‐Spirobifluorene‐based closo‐o‐carboranyl (SFC1 and SFC2) compounds and their nido‐derivatives (nido‐SFC1 and nido‐SFC2) were prepared and characterized. The two closo‐compounds displayed major absorption bands assignable to π–π* transitions involving the spirobifluorene group, as well as weak intramolecular charge‐transfer (ICT) transitions between the o‐carboranes and their spirobifluorene moieties. The nido‐compounds exhibited slightly blueshifted absorption bands resulting from the absence of the ICT t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 63 publications
0
36
0
Order By: Relevance
“…As f w was 95%, the λ em value of o-1 had an obvious blue shift by 31 nm with respect to f w of 90%, while o-2 was only slightly blue shifted by 9 nm [28]. It was clearly demonstrated that the red-shifted spectra were attributed to the lowest TICT excited states [30]. On the other hand, the selective introduction of ocarborane units onto the BINOL skeletons also exerted influence on their aggregated patterns, resulting in different aggregation-induced emission-(AIE-) active properties.…”
Section: Resultsmentioning
confidence: 92%
“…As f w was 95%, the λ em value of o-1 had an obvious blue shift by 31 nm with respect to f w of 90%, while o-2 was only slightly blue shifted by 9 nm [28]. It was clearly demonstrated that the red-shifted spectra were attributed to the lowest TICT excited states [30]. On the other hand, the selective introduction of ocarborane units onto the BINOL skeletons also exerted influence on their aggregated patterns, resulting in different aggregation-induced emission-(AIE-) active properties.…”
Section: Resultsmentioning
confidence: 92%
“…The planar conformation of the conjugated system and perpendicular orientation of the C−C bond in the o ‐carborane and π‐planes are favorable for presenting AIE with ICT character. Moreover, AIE efficiency was examined with spirobifluorene‐tethered o ‐carboranes and nido ‐carboranes ( 38 – 41 ) . It was mentioned that the perpendicular orientation is also advantageous for obtaining higher efficiency of AIE.…”
Section: Aggregation‐induced Emissionmentioning
confidence: 99%
“…Fox et al showed that the D-A dyad, C-diazaboryl-o-carborane, exhibits two different excited states (locally excited (LE) and ICT transition states), depending on the rotational motion of diazaboryl derivatives; 26 this phenomenon is called the twisted intramolecular charge-transfer (TICT) effect. [46][47][48][49][50][51][52][53][54][55][56] The occupation of the lowest unoccupied molecular orbital (LUMO) levels for an o-carborane cage is dramatically altered from 36% to 98% in accordance with the motion. This indicates that the electronic separation between the donor and acceptor moieties is governed by structural motion.…”
Section: Introductionmentioning
confidence: 99%